2010
DOI: 10.1097/iae.0b013e3181c703fc
|View full text |Cite
|
Sign up to set email alerts
|

Factors Correlated With Postoperative Visual Acuity After Vitrectomy and Internal Limiting Membrane Peeling for Myopic Foveoschisis

Abstract: Pars plana vitrectomy with internal limiting membrane peeling results in long-term favorable anatomical and visual outcomes. Eyes with an FD may be good candidates for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
66
6
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 39 publications
(57 reference statements)
12
66
6
4
Order By: Relevance
“…However, a better postoperative BCVA has been reported to be correlated with a better preoperative BCVA and shorter axial length. [25][26][27] Macular holes were detected intraoperatively in the FD group, but some of these MHs may have existed preoperatively and not detected by an OCT because the holes were covered with premacular fibrotic tissues.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, a better postoperative BCVA has been reported to be correlated with a better preoperative BCVA and shorter axial length. [25][26][27] Macular holes were detected intraoperatively in the FD group, but some of these MHs may have existed preoperatively and not detected by an OCT because the holes were covered with premacular fibrotic tissues.…”
Section: Discussionmentioning
confidence: 88%
“…25 Consequently, vitrectomy has been recommended when patients experience an FD with symptomatic visual impairiments. 25,26 The development of an MH or MHRD is a major complication that is associated with poor postoperative vision. 17,20 Our results showed that an MH developed intraoperatively but not postoperatively in the FD group, although an MHRD did develop postoperatively in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Dyes should be used for ILM removal in highly myopic eyes because the ILM is transparent and fragile in these cases. In recent studies, the dyes used for the peeling of ILM in foveoschisis were triamcinolone acetonide or indocyanine green [20,21,22], and not Brilliant Blue G. In fact, indocyanine green has recently been reported to have a potential retinal toxicity compared with Brilliant Peel in an experimental study [23]. In our opinion, Brilliant Blue G staining should be considered in all cases with myopic foveoschisis to make the surgery easy and effective, and can lead to anatomical success as we report.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that have been found to be correlated with a poorer prognosis by Kumagai and Larson et al in a retrospective study of 39 eyes undergoing vitrectomy and ILM peel were foveal detachment, high axial length, and poor pre-operative visual acuity. 37 The controversy around the risks of ILM peel was addressed by Zheng and Shen et al in a retrospective series and literature review. 41 They concluded that vitrectomy and ILM peel did not increase the risk of iatrogenic macular hole formation and that gas tamponade with C3F8 resulted in more rapid foveal reattachment and better improvement of visual acuity postoperatively.…”
Section: Managementmentioning
confidence: 99%